Support Spaces. An Anthropological Approach to Selected Design Solutions in Support Institutions - Inga B. Kuźma (Nauki o Wychowaniu, 2019)
The article presents conclusions from research on the space of support institutions. The authors use mainly the tools of cultural anthropology and proxemics. The authors used three examples known to them from their projects on homeless people and those endangered by other types of social exclusion: BSZMKI from Budapest, one of the Krakow St. Padre Pio Aid Centers and Gdansk House, located in the Dolne Młyny area. The authors show how these buildings are constructed, how places are created there with a special character, to what extent the idea of support, which every institution pursues by implementing a specific program, goals and missions, translates into spatial and aesthetic relations and what kind of ethics it produces. They also show the possibilities of anthropological and proxemic approach to decipher the “hidden curriculum” embodied by each institution, also in a spatial context. According to the authors, this kind of analysis of material data along with the interpretation of the rules of using the building and spatial order, which is observed inside the institution, may support reflection on the course of support offered in institutions run by specific organizations.